Anodal transcranial direct current stimulation to the cerebellum improves handwriting and cyclic drawing kinematics in focal hand dystonia - Bradnam, Lynley V.; Graetz, Lynton J.; McDonnell, Michelle N.; Ridding, Michael C. (Frontiers in Human Neuroscience, 2015)
There is increasing evidence that the cerebellum has a role in the pathophysiology of primary focal hand dystonia and might provide an intervention target for non-invasive brain stimulation to improve function of the affected hand. The primary objective of this study was to determine if cerebellar transcranial direct current stimulation (tDCS) improves handwriting and cyclic drawing kinematics in people with hand dystonia, by reducing cerebellar-brain inhibition evoked by transcranial magnetic stimulation (TMS). Eight people with dystonia (5 writer’s dystonia, 3 musician’s dystonia) and eight age-matched controls completed the study and underwent cerebellar anodal, cathodal and sham tDCS in separate sessions. Dystonia severity was assessed using the Writer’s Cramp Rating Scale and the Arm Dystonia Disability Scale. The kinematic measures that differentiated the groups were; mean stroke frequency during handwriting and fast cyclic drawing and average pen pressure during light cyclic drawing. TMS measures of cortical excitability were no different between people with FHD and controls. There was a moderate, negative relationship between TMS-evoked cerebellar-brain inhibition at baseline and the Writer’s Cramp Rating Scale in dystonia. Anodal cerebellar tDCS reduced handwriting mean stroke frequency and average pen pressure, and increased speed and reduced pen pressure during fast cyclic drawing. Kinematic measures were not associated with a decrease in cerebellar-brain inhibition within an individual. In conclusion, cerebellar anodal tDCS appeared to improve kinematics of handwriting and circle drawing tasks; but the underlying neurophysiological mechanism remains uncertain. A study in a larger homogeneous population is needed to further investigate the possible therapeutic benefit of cerebellar tDCS in dystonia.